integrated genetic linkage map of the laboratory rat - M. Brown , , Tara C. Matise, Donna; Koike, George; Simon, Jason S.; Winer, Eric S.; Zangen, Sarah; McLaughlin, Michael G.; Shiozawa, Masahide; Atkinson, O. Scott; Jr, James R. Hudson; Chakravarti, Aravinda; S. Lander , , Howard, Eric (Mammalian genome, 1998)
The laboratory rat, Rattus novegicus, is a major model system for physiological and pathophysiological studies, and since 1966 more than 422,000 publications describe biological studies on the rat (NCBI/Medline). The rat is becoming an increasingly important genetic model for the study of specific diseases, as well as retaining its role as a major preclinical model system for pharmaceutical development. The initial genetic linkage map of the rat contained 432 genetic markers (Jacob et al. 1995) out of 1171 developed due to the relatively low polymorphism rate of the mapping cross used (SHR × BN) when compared to the interspecific crosses in the mouse. While the rat genome project continues to localize additional markers on the linkage map, and as of 11/97 more than 3,200 loci have been mapped. Current map construction is using two different crosses (SHRSP × BN and FHH × ACI) rather than the initial mapping cross. Consequently there is a need to provide integration among the different maps. We set out to develop an integrated map, as well as increase the number of markers on the rat genetic map.The crosses available for this analysis included the original mapping cross SHR × BN reciprocal F2 intercross (448 markers), a GH × BN intercross (205 markers), a SS/Mcw × BN intercross (235 markers), and a FHH/Eur × ACI/Hsd intercross (276 markers), which is also one of the new mapping crosses. Forty-six animals from each cross were genotyped with markers polymorphic for that cross. The maps appear to cover the vast majority of the rat genome. The availability of these additional markers should facilitate more complete whole genome scans in a greater number of strains and provide additional markers in specific genomic regions of interest.